Basic moral sensitivity, moral disengagement, and defender self-efficacy as predictors of students’ self-reported bystander behaviors over a school year: a growth curve analysis - Sjögren, Björn; Thornberg, Robert; Kim, Jingu; Hong, Jun Sung; Kloo, Mattias (Frontiers in Psychology, 2024)
Though school children tend to view peer victimization as morally wrong most do not to intervene on the victim’s behalf and some instead choose to aid the victimizer. The aim of this longitudinal study was to investigate how students’ defending and pro-aggressive bystander behaviors evolved over the course of one school year and their association to basic moral sensitivity, moral disengagement, and defender self-efficacy. Three-hundred-fifty-three upper elementary school students (55% girls; 9.9–12.9 years of age) each completed self-report surveys at three points during one school year. Results from latent growth curve models showed that pro-aggressive bystander behavior remained stable over the year, whereas defending behavior decreased. Moreover, students who exhibited greater basic moral sensitivity were both less likely to be pro-aggressive and simultaneously more likely to defend. Students with defender self-efficacy were not only associated with more defending behavior at baseline but also were also less likely to decrease in defender behavior over time. Conversely, students reporting a higher degree of moral disengagement were linked to more pro-aggressive behavior, particularly when also reporting lower basic moral sensitivity. These short-term longitudinal results add important insight into the change in bystander behavior over time and how it relates to students’ sense of morality. The results also highlight the practical necessity for schools to nurture students’ sense of morality and prosocial behavior in their efforts to curb peer victimization.